Pemberdayaan Ibu Hamil melalui Literasi Buku KIA dalam Upaya Deteksi Dini dan Pencegahan Komplikasi Kehamilan di Klinik Pratama Sarfina Kota Medan - Sonia Novita Sari; Sri Murtini; Nova Isabella Mariance Br Napitupulu; Leni Oktafianti; Kezia S.A. Rajagukguk; Nabila Rara Putri; Azahra Azahra (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
The Maternal Mortality Rate (MMR) is primarily caused by pregnancy complications that are actually preventable through early detection; however, maternal understanding of the Maternal and Child Health (MCH) Handbook remains very low. This community service aims to empower pregnant women at Sarfina Primary Clinic, Medan, by enhancing their MCH Handbook literacy. The implementation utilized a Community-Based Participatory Action (CBPA) approach conducted over four weeks, involving 30 pregnant women. The activity stages included a pre-test, interactive education, self-assessment simulations, and a post-test. Evaluation results indicated a significant surge in health literacy; pregnant women's knowledge in the "Good" category drastically increased from 13.3% to 86.7%, while the "Poor" knowledge category was successfully eliminated from 50% to 0%. In conclusion, this educational and simulation intervention proved highly effective in transforming pregnant women's behavior, making them proactive individuals in the early detection of pregnancy danger signs which is expected to reduce the risk of pregnancy complications and reduce maternal mortality rates.